Some problems of cattle breeding in the Republic of Kazakhstan - Shulanbekova, G.K.; Kuanaliyeva, G.A. (Journal of actual problems of jurisprudence, 2018)
At present, by the number of cattle in the lead – India, Brazil, the US, China and Argentina, and milk production – India, USA, China, Germany and Brazil. Kazakhstan took complex measures for strengthening of an export potential of meat cattle breeding in 2010, when problems of expansion of export of real sector, strengthenings of a role of small and medium business in production of goods and services, and also prospects of regional development were put forward as key priorities of economic policy of the state. Key words: cattle breeding, export of meat, import of meat, legal regulation of animal husbandry.